Web Based He Live Doc Application System Design Analysis - Muqorobin, Muqorobin; Indriastiningsih, Erna (Institut Teknologi Bisnis AAS Indonesia, 2024)
This research focuses on the design and development of the He Live Doc application, a web-based document management platform that supports real-time collaboration. Using a prototyping method with a user-centered design approach, this research aims to create a solution that increases productivity and efficiency in document management. The research methodology involves user needs analysis, system design, prototype development, and user evaluation. Results show a 30% increase in efficiency compared to traditional methods, with user satisfaction levels reaching 85%. The app offers a responsive interface, secure authentication system, real-time collaboration features, version control, and cloud storage integration. The main challenge identified was performance optimization for simultaneous editing by multiple users. This research contributes to the development of document collaboration technology and opens opportunities for further research in performance optimization and integration of artificial intelligence